Heparin-induced thrombocytopenia (HIT II) - a drug-associated autoimmune disease - Nowak, Götz (Thrombosis and haemostasis, 2009)
Autoimmune thrombocytopenia (ITP) is an acquired autoimmune disease characterised by isolated persistent thrombocytopenia and normal megakaryopoiesis. This definition also applies to heparin-induced thrombocytopenia (HIT II), a frequent side effect of heparin treatment. In HIT II, the immunogen is a coagulation active complex of heparin and platelet factor 4 (PF4). By now, diagnostics of HIT II is often material and time consuming. Three groups of patients were investigated for HIT II antibodies (HIT II-AB): 54 hospitalised stroke patients, 87 hospitalised cardiac patients, and 71 patients on chronic haemodialysis, all treated with heparin. Furthermore, 100 healthy volunteers were investigated. For detection of HIT II-AB the innovative whole blood test PADA-HIT (PADA: platelet adhesion assay) was used. PADA-HIT quantifies the interaction of IgG antibodies with FcgammaIIA receptors by comparing the activation state of platelets in citrated and heparinised whole blood. The occurrence of HIT II-AB in blood was very high with 44 % of stroke patients, 69% of cardiac patients and 38% of haemodialysis patients compared to only 15% of healthy volunteers. This demonstrates a high incidence and a rapid onset of HIT II-AB in patients being acutely treated with heparin. HIT II is one of the most frequent and severe autoimmune diseases bearing a great thrombosis risk. PADA-HIT represents an innovative diagnostic method for detection of autoimmune antibodies of IgG type that are directed against platelet factor 4 (PF4)-heparin-complex. By early and fast diagnostics and appropriate treatment severe complications of HIT II can be prevented.